Examining the Impact of Tutor Effectiveness and Student Motivation on Academic Achievement in Package C Programs: An Analysis of Community Learning Centers in Ambon City - Arnold Sahalessy; John Rafafy Batlolona; Lambertus J Lakollo; Abednego Abednego (AL-ISHLAH: Jurnal Pendidikan, 2025)
Tutor effectiveness is a critical factor in non-formal education, particularly in the Package C equivalency program. One of the major challenges in this context is low student motivation, which significantly affects academic achievement.This study employed a descriptive quantitative approach to examine the influence of tutor performance and student learning motivation on academic achievement in the Package C program in Ambon City. Data were collected through questionnaires distributed to 90 tutors across four Community Learning Activity Centers (Pusat Kegiatan Belajar Masyarakat, PKBM) in the Sirimau sub-district.The analysis showed that both tutor performance (t = 5.009, p .05) and student learning motivation (t = 1.998, p .05) had a significant positive effect on student achievement. Additionally, tutor competence and work motivation were found to significantly influence overall tutor performance (F = 14.922, p .05).These findings highlight the dual importance of enhancing tutor effectiveness and fostering student motivation to improve educational outcomes in non-formal settings. Tutor performance is shaped by internal factors such as professional competence and motivation, which in turn impact students' academic success.Tutor performance and student learning motivation are key predictors of student achievement in the Package C program. Future interventions should prioritize capacity building for tutors and strategies to increase student engagement in non-formal education environments.